A survey on the consumer knowledge of organic cosmetics at Can Tho City in 2022-2023 - Hưng , Nguyễn Phục; Khoa, Lý Đăng; Phú, Mạc Thiên; Nguyên , La Nữ Kiều; Nhi , Trần Thị Tuyết; Uy, Nguyễn Huỳnh Thanh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Background: The organic cosmetics market in Vietnam has been developing for a long time. However, to have a more objective view of the organic cosmetics market, a comprehensive understanding of the market for organic cosmetics is necessary to provide development directions that are genuinely correct, unfortunely there isn’t much research to support it. Therefore, studying the knowledge of organic cosmetic consumers will aid in the advancement of both intellectual and economic domains. Objectives: The purpose of study is to assess knowledge about organic cosmetics of consumers in Can Tho City. Materials and methods: The present study used a cross-sectional descriptive method, based on using a cross-sectional descriptive design, interviewing 559 organic cosmetics consumers in Can Tho City using a set of interview questions to assess consumers’ knowledge of organic cosmetics. Results: The majority of consumers aged 18 to 25 (72.1%) are interested in and use organic cosmetic products more than other ages. Women consumers was found with higher proportion (70.7%) than men consumer (29.3%). Most consumers have average or higher knowledge with a proportion of (61.4%). The study also found that medical staff have better knowledge about organic cosmetics than other groups. Conclusions: The results of the study have shown that the majority of people have good knowledge, but there are many who are not. However, whether or not this knowledge status is connected to the intention to purchase organic cosmetics requires further research.